2013
DOI: 10.3791/50852
|View full text |Cite
|
Sign up to set email alerts
|

Handwriting Analysis Indicates Spontaneous Dyskinesias in Neuroleptic Naïve Adolescents at High Risk for Psychosis

Abstract: Growing evidence suggests that movement abnormalities are a core feature of psychosis. One marker of movement abnormality, dyskinesia, is a result of impaired neuromodulation of dopamine in fronto-striatal pathways. The traditional methods for identifying movement abnormalities include observer-based reports and force stability gauges. The drawbacks of these methods are long training times for raters, experimenter bias, large site differences in instrumental apparatus, and suboptimal reliability. Taking these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…Because of the putative neurobiological mechanisms linking spontaneous dyskinesia with schizophrenia 31, 32 , some have explored the sensitivity of quantifying handwriting movement dysfluencies as an alternative. In one such study of adolescents at high risk for schizophrenia 33 , investigators found that those identified has having a prodromal or ultra-high risk syndrome had significantly higher mean scores on the ANJ measure for complex loops. Their findings suggest that dysfluent handwriting movements may also serve as an early behavioral biomarker of schizophrenia in high risk adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the putative neurobiological mechanisms linking spontaneous dyskinesia with schizophrenia 31, 32 , some have explored the sensitivity of quantifying handwriting movement dysfluencies as an alternative. In one such study of adolescents at high risk for schizophrenia 33 , investigators found that those identified has having a prodromal or ultra-high risk syndrome had significantly higher mean scores on the ANJ measure for complex loops. Their findings suggest that dysfluent handwriting movements may also serve as an early behavioral biomarker of schizophrenia in high risk adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, more positive numbers (i.e., values closer to zero) indicate that the right hand was more similar to the left hand, suggesting decreased dextrality. Of note, a subset of the current participants have also completed two separate studies aimed at understanding hyperkinetic and hypokinetic movement abnormalities associated with risk for psychosis using MoveAlyzer software (Dean and Mittal, 2015; Dean et al, 2013). These studies were not focused on laterality and did not use the same kinematic variables.…”
Section: Methodsmentioning
confidence: 99%
“…While these methods provide excellent classification, they may miss subtle variations in handedness because they rely on self and observer reports. Recent efforts to understand movement abnormalities in psychosis and at risk populations using computer based handwriting measures may provide an objective method for assessing subtle abnormalities in handedness (Caligiuri et al, 2009; Caligiuri et al, 2010; Dean and Mittal, 2015; Dean et al, 2013; Docx et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Our group has begun to employ strain gauge and handwriting kinematic assessments of motor pathology, which provide continuous variables that are more sensitive than observer-based methods, identifying individuals with overt dyskinesias as well as those who only have subclinical movement pathology (Cortese et al, 2005; Dean and Mittal, 2015; Dean et al, 2016; Dean et al, 2013). Our earlier work combining observer-based ratings of dyskinetic movement abnormalities with cognitive deficits in adolescents with prodromal syndromes showed some promise for predicting psychosis (sensitivity= 60.0%, specificity = 76.0%, PPV = 43.0%, NPV = 86.3%) (Mittal et al, 2010).…”
Section: Incorporating Developmentally Informative Assessments Into Rdocmentioning
confidence: 99%